Dialectic Of Social Change: A Comprehensive Analysis Of Piotr Sztompka's Thought In The Dynamics Of Modern Society - Rizqina Fijriah; Jasmidar Jasmidar; Athaya Shakila Ramadhani (Journal of Health and Multidisciplinary Health Studies, 2026)
Social change is the subject of study of sociology that studies how society transforms from one state to another. This article discusses in detail Piotr Sztompka's thoughts on the sociology of social change. The main focus includes the deconstruction of the concept of change, the debate between evolution and revolution, the role of human agency through social movements, and the impact of globalization on the structure of society. Through the literature study method, the results of the research are: (1) this article aims to explain Sztompka's synthesis of the dialectical relationship between structural factors and the creative actions of agencies in encouraging historical change; (2) Identify the importance of social becoming theory in understanding the transition of contemporary society from the isolation phase to the era of globalization and cultural hybridity. The results of the paper conclude that contemporary social change is the result of the complex interaction between structural factors and human creative actions (agencies) that give birth to history. The novelty of this article is that it presents a reconstruction of Sztompka's thought integrated with the phenomenon of new digital social movements, as well as offering an alternative point of view that bridges structural determinism and agency voluntarism in the context of postmodern society.